Integrating sustainability practices into islamic corporate governance for sustainable firm performance: from the lens of agency and stakeholder theories - Jan, A.A. (Springer Science and Business Media B.V., 2021)
While the literature indicates that Islamic Corporate Governance (ICG) practices enhance firm performance, there is scant research on how sustainability practices affect the nexus between ICG and firm performance. To address this knowledge gap, this study developed a framework for conceptualizing the moderating effect of sustainability practices on the relationship between Islamic corporate governance and firm performance. This study incorporated sustainability practices into the ICG framework to evaluate their impact on firm performance by integrating agency and stakeholder theories. This study derived the most important factors from the theoretical perceptions of these two theories and, as a result, established their nexus through the development of research propositions. This study contributes to the body of knowledge on Islamic banking by presenting a novel approach for incorporating sustainability practices into an ICG framework that improves firm performance. Along with adding to the scant body of knowledge on Islamic corporate governance and sustainability, this research gives critical insights to policymakers and concerned stakeholders, particularly Accounting and Auditing Organization for Islamic Financial Institutions, on how to adopt sustainable governance policies/standards and improve existing standards. To the authorsâ knowledge, this is the first study to integrate sustainability practices into ICG in order to promote the sustainability of Islamic banks and financial institutions. Â© 2021, The Author(s), under exclusive licence to Springer Nature B.V.